2020
DOI: 10.1002/adsc.202000553
|View full text |Cite
|
Sign up to set email alerts
|

Imidazodipyridines via DMAP Catalyzed Domino N−H Carbonylation and 6π‐Electrocyclization: Synthetic Scope and Application

Abstract: In this work, we report a domino reaction for access to highly functionalized imidazo[1,2‐a:5,4‐b′]dipyridines simply by stirring Boc2O in the presence of DMAP as a catalyst with readily prepared 3‐amino‐2‐(vinyl)imidazo[1,2‐a]pyridine. This methodology enables the synthesis of highly functionalized imidazodipyridines. The process proved to be compatible with a wide variety of substrates. The synthetic potential of this method was illustrated by performing a Suzuki‐Miyaura coupling on 4‐phenylimidazo‐dipyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, it was observed that the formation of the amine intermediate occurred in the presence of a wet solvent, as previously reported in our work. 31…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was observed that the formation of the amine intermediate occurred in the presence of a wet solvent, as previously reported in our work. 31…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was observed that the formation of the amine intermediate occurred in the presence of a wet solvent, as previously reported in our work. 31 Concerning the formation of DINI derivatives, the nitro compound 3k underwent conversion to the DINI derivative in a 72% yield within 6 h under the standard conditions (Scheme 5f). In the absence of Mo-catalyst, the reaction proceeded, albeit at a slower rate, requiring 48 hours for completion (Scheme 5g).…”
Section: Resultsmentioning
confidence: 99%
“…Alami, Hamze, and co-workers 62 reported a novel methodology for the synthesis of 3-aryl-1 H -pyrroloimidazo[1,2- a ]pyridines 87 by the cross-coupling of 3-nitro-2-(arylvinyl)imidazo[1,2- a ]pyridines 86 with N -tosylhydrazones 16 and followed by Cadogan reductive conditions (Scheme 31 ). The optimized one-pot reaction conditions were: step 1: N -tosylhydrazone 16 (1 mmol), 86 (1 mmol), catalyst Pd 2 dba 3 ·CHCl 3 (2.5 mol%), XPhos ligand (5 mol%), LiO t Bu base (2.2 mmol), in 1,4-dioxane solvent in a sealed tube under microwave irradiation at 110 °C for 30 mins; step 2: catalyst MoO 2 Cl 2 (dmf) 2 (10 mol%) and ligand PPh 3 (4 equiv) were added and the mixture was placed under MW irradiation at 135 °C for ~4 h; and step 3: (Boc) 2 O (1.3 mmol), DMAP (0.2 mmol), and Et 3 N base (3 mmol) were added, and the mixture was stirred at room temperature for 2 h. Electronic effects in the N -tosylhydrazones did not affect the yields of the reactions and various heterocyclic N -tosylhydrazone also gave the products in good yields.…”
Section: Applications Of N -Tosylhydrazonesmentioning
confidence: 99%
“…Li et al 7 and Zhang et al 29 also reported on the utility of some imidazo[1,2-a]pyridin-3-amines as precursors for the synthesis of imidazo[1,2-a:5,4-b']dipyridines.…”
Section: Synthesismentioning
confidence: 99%